Energy generation characteristics of pressure retarded osmosis using polymer solution - Kiyoshi BANDO; Ryoko OTOMO; Yuma SUZUKI; Takamori SHIOMI; Yusuke NISHIZAKI (Journal of Fluid Science and Technology, 2022)
Research on energy generation characteristics based on pressure retarded osmosis (PRO) using seawater is being widely carried out. However, there are few studies that use polymer solutions. Therefore, the purpose of this study is to evaluate energy generation characteristics when using a polymer solution. We established a PRO model with a constant hydrostatic pressure difference in a semipermeable membrane, through which pure water permeates into the polymer solution side. The concentration of the polymer solution was determined by solving the one-dimensional convection-diffusion equation, and the osmotic pressure difference in the semipermeable membrane was evaluated. The following four dimensionless parameters were derived by making the basic equations dimensionless; the dimensionless second virial coefficient α, the dimensionless hydrostatic pressure difference p*, the Péclet number Pe, and the cross-sectional area reduction ratio of the tube on the solution side β. The generation characteristics of dimensionless power densities were evaluated by changing the α representing the properties of the polymer solution. The value of p* for which the largest dimensionless power density obtained was 0.5 or more, and approached 1 as α increased. When compared with seawater, the power density while using polymer solution was smaller than that while using seawater. However, by preventing the temporal decrease in the concentration of the polymer solution and the generation of a concentration boundary layer, it is possible to significantly improve the power density and obtain a power density close to that of seawater. In addition, when the membrane used for standard PRO is applied to the present model, a commercial-level power density can be obtained.